PENGARUH KETERAMPILAN WIRAUSAHA DAN SPIRITUALITAS TERHADAP KINERJA ORGANISASI UKM SEKTOR KULINER DI KOTA SURABAYA - Tony Susilo Wibowo (Fakultas Ekonomi dan Bisnis, 2020)
Small and Medium Enterprises (SMEs) is one important element in boosting the Indonesian economy, especially in the culinary sector. The Indonesian Agency for Creative Economyreleased data in 2015 the contribution of the creative economy to the Gross Domestic Product (GDP) of Rp 852 trillion and 8.2 million units are creative industries, and 68% are in the culinary sector and contribute to the GDP of 41.69%.On the other hand, the existence of SMEs must be supported by entrepreneurial abilities that are reflected in entrepreneurial skills as well as the characteristics of Indonesian society that attach elements of faith through spirituality. This research aims to analyze and describe the influence of entrepreneurial skills and spirituality variables on organizational performance in SMEs. This research approach is quantitative with a questionnaire instrument. Data processing uses multiple linear regression statistical analysis. The study was conducted at the Culinary Tourism Center of Al Akbar Mosque, located on Jalan Menanggal with a period of September - October 2019. After going through descriptive statistical testing, it is known that the entrepreneurial skills variable has a beta value of 0.225 with a significance level of 0.192 and> 0.05 so that the entrepreneurial skills variable does not affect the performance of SME organizations. For testing with spirituality variables, it is known that the beta value of 0.621 with a significance level of 0.011 <0.005 so that spirituality influences the performance of SME organizations. From the tests conducted simultaneously, the variables of entrepreneurial skills and spirituality affect the performance of SME organizations.